Numerical study on wind profiles change trend of upright reticulation barriers under different configuration models - Dang, Xiaohong; Chi, Xu; Tang, Guodong; Meng, Zhongju; Huang, Haiguang; Zhai, Bo; Yuan, Limin (Frontiers in Environmental Science, 2023)
To explore how to lay the same specifications to maximize the protection benefits of mechanical sand barriers is an essential issue in the actual production process. We used the Reynolds-Averaged Navier-Stokes (RANS) method and the shear stress transport (SST) K-ε turbulence model to study the windbreak efficiency of sand barriers with different structures. Among them, the structure of the sand barriers includes rhombus 60° (cTnI = 60°, R60°), rhombus 90° (cTnI = 90°, R90°), rhombus 120° (cTnI = 120°, R120°) and parallel straight line (belt). The sand barrier was set to a porous jump model, where the surface permeability a was 2.6 × 108, and the inertial resistance coefficient c2 was 9,400. The wind velocity field results showed that the sand barrier’s blocking effect on wind velocity decreases with the increase in height. The leading edge of the 120° obstacle has the strongest weakening effect on the inlet wind speed. The minimum wind speed (0.97 m/s to 1.41 m/s) occurs near the sand barrier, and the vortex appears on both sides of the node, and the wind speed increases. The order of the blocking effect of different angles on airflow is as follows: 120° > 90°> brand >60°. Under R120° conditions, the wind speed is reduced by more than 60% at 0.05 m and 0.1 m height behind the barrier compared to the initial wind speed. This will be conducive to the design and control engineering planning of the laying angle of the gauze sand barrier in the main wind direction.